Thermoplastic composite material capable of absorbing X-rays and preparation method thereof
Through the modification of nano X -ray shielding materials and the introduction of modified graphene and sodium sodium sodium group, the problem of the existing materials in compatibility and dispersability was solved, and the efficient X -ray shielding and excellent mechanical performance were achieved Essence
Patent Information
- Application Number
- CN202411969000.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
AI Technical Summary
The existing X-ray shielding materials have poor compatibility and dispersion with thermoplastic polymer matrix, resulting in poor shielding effect and mechanical properties of composite materials.
By using Silicane Trimmeter to modify the nano GD2O3, BI2O3 and other X -ray shielding materials, it enhances the compatibility and decentralization of thermoplastic substrates such as polyethylene polyethylene, and introduces the division of modified graphene and sodium sodium sodium sodium sodium sodium group. , Improve the decentralization of materials and the combination of interface.
The effective dispersion and stability of the nano -shielding materials after refined, and ensure that the composite materials also have excellent mechanical performance and lightweight design while maintaining a high shielding effect.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a thermoplastic composite material capable of absorbing X-rays and a preparation method thereof. Background Art
[0002] With the rapid development of modern science and technology, X-rays have been widely used in medical diagnosis, non-destructive testing, scientific research and other fields. However, the strong penetration and potential harm of X-rays pose a threat to people's health and safety. Therefore, it is particularly important to develop an efficient, lightweight and stable X-ray shielding material.
[0003] Traditional X-ray shielding materials, such as lead plates and lead glass, have good shielding effects, but they have disadvantages such as high density, fragility, and difficulty in processing, which limit their widespread application. In recent years, researchers have begun to explore the use of new inorganic materials, such as Gd2O3, Bi2O3, LaB6, etc. These materials have high atomic numbers and good X-ray absorption capabilities and are ideal X-ray shielding materials. However, these inorganic materials have poor compatibility with thermoplastic polymer matrices such as polypropylene and are difficult to disperse evenly in the matrix, resulting in poor shielding effects and mechanical properties of the composite materials. In order to solve this problem, researchers have refined nanoscale X-ray shielding materials, increasing their specific surface area and contact area with X-rays by reducing the particle size, thereby improving the shielding effect. However, the refined nano-shielding materials are more likely to agglomerate, resulting in reduced dispersibility in the matrix, which in turn affects the overall shielding effect of the composite material.
[0004] Based on the above statements, the present application provides a thermoplastic composite material capable of absorbing X-rays and a preparation method thereof. Summary of the invention
[0005] In order to solve the problems raised by the background technology, the present application provides a thermoplastic composite material that can absorb X-rays and a preparation method. A silane coupling agent is used to modify X-ray shielding materials such as nano Gd2O3 and Bi2O3, and its compatibility and dispersibility with thermoplastic matrices such as high molecular weight polyethylene are enhanced through chemical bonding. At the same time, modified graphene and sodium humate components are introduced, and the two-dimensional structure of graphene and the functional groups of sodium humate are used to form interactions with the nano shielding material and the matrix, thereby further improving the dispersibility and interfacial bonding strength of the material. The effective dispersion and stabilization of the refined nano shielding material is achieved, ensuring that the composite material has excellent mechanical properties and lightweight design while maintaining a high shielding effect.
[0006] The present application provides a thermoplastic composite material capable of absorbing X-rays and a preparation method thereof, which adopts the following technical scheme: A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1, taking a graphene oxide raw material, reducing it with a reducing agent, and preparing modified graphene; S2, performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material; S3, mixing the modified graphene, modified nano-shielding material and sodium humate solution obtained in step S1, and then inputting them into a forced air drying oven to dry at 50-80°C for 2-3 hours, and then mixing them with a thermoplastic polymer matrix to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays.
[0007] Preferably, in step S1, the modified graphene is prepared by the following steps: The graphene oxide is placed in deionized water and centrifuged for 3-5 minutes, and then a reducing agent is added to the system and treated at 70-90° C. for 8-16 hours to obtain modified graphene.
[0008] Further, in step S1, the modified graphene is specifically prepared by the following steps: Graphene oxide is placed in deionized water at a mass volume ratio of 1 g:100 mL, and centrifuged at 6000-9000 rpm for 3-5 minutes. A reducing agent is then added to the system, and the system is treated at 70-90° C. for 8-16 hours to obtain modified graphene.
[0009] In the above reaction process, the graphene oxide is treated with a reducing agent to remove the oxygen-containing functional groups on the graphene oxide, thereby preparing modified graphene.
[0010] Furthermore, the usage amounts of graphene oxide and reducing agent are 1 g:(0.8-1.2) g.
[0011] Furthermore, in step S1, the reducing agent used is 80 wt % hydrazine hydrate solution.
[0012] Preferably, the modified nano-shielding material is prepared by the following steps: The nano-shielding material is placed in an ethanol solution and ultrasonically treated for 10-30 minutes at room temperature, then the pH value of the system is adjusted to 3-4, a silane coupling agent is added, and the system temperature is increased to 70-90°C. After treatment for 8-10 hours, the solution is centrifuged, the precipitate is collected, washed, and dried to obtain the modified nano-shielding material.
[0013] Furthermore, the modified nano-shielding material is specifically prepared by the following steps: The nano-shielding material is placed in a 80-90wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated at room temperature for 10-30 minutes, with the ultrasonic frequency set to 20-22KHz, and then an acetic acid solution is added to adjust the pH value of the system to 3-4, a silane coupling agent is added, and the system temperature is increased to 70-90°C. After treating for 8-10 hours, the solution is centrifuged at a speed of 3000-5000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material.
[0014] In the above reaction process, the nano-shielding material is modified by using a silane coupling agent, and a silicon-oxygen-metal bond is formed through the hydrolysis and condensation process of the silane coupling agent. In the process, the silane coupling agent introduces hydrophobic organic groups to the surface of the metal oxide powder. These hydrophobic groups can significantly reduce the surface energy of the metal oxide powder, making it exhibit hydrophobic properties.
[0015] Furthermore, the nano shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 in a mass ratio of 1:(3-5):(1-2), and the particle size is 30-60nm.
[0016] Furthermore, the mass ratio of the nano-shielding material, the acetic acid solution and the silane coupling agent is 1:5:(0.05-0.1).
[0017] Furthermore, in step S3, the mixed material is prepared by the following steps: The modified graphene and modified nano-shielding material obtained in step S1 are added to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of (0.1-1) g: (0.1-1) g: (5-10) mL, mixed at room temperature, and then input into a forced air drying oven and dried at 50-80° C. for 2-3 hours. The dried product is then mixed with a thermoplastic polymer matrix in a mass ratio of (10-40): (70-80) and a speed of 30-90 rpm to obtain a mixture.
[0018] Furthermore, in step S3, the thermoplastic polymer matrix is high-density polyethylene.
[0019] In summary, this application has the following beneficial effects: 1. In the technical solution of the present invention, Gd2O3, Bi2O3, LaB6 and graphene are used to obtain the X-ray shielding material in the product. The atomic number of the metal atoms in Gd2O3 and Bi2O3 is high and can effectively absorb X-rays. LaB6 also has a certain absorption effect on X-rays and has good mechanical properties and thermal stability. It is used as a reinforcing material to improve the strength of the overall structure. The modified graphene component retains the unique two-dimensional structure of graphene, which can effectively increase the interaction area between its shielding material and X-rays, effectively absorb and convert X-rays, and can achieve a high shielding effect while achieving a lightweight design.
[0020] 2. In the technical solution of the present invention, a reducing agent is used to modify graphene oxide, which reduces the oxygen-containing functional groups on graphene oxide, so that it has better compatibility and more uniform dispersion effect with the hydrophobic thermoplastic polymer matrix and the nano-shielding material, and at the same time reduces the further cross-linking of the high-density matrix caused by the graphene oxide matrix, and prevents the increase of its cross-linking points, the decrease of toughness, and the decrease of its mechanical properties. In addition, a sodium humate component is added to the system. Sodium humate contains a large amount of catechol structures, which can promote the dispersion of the nano-shielding material through the form of metal ion coordination bonds, and the benzene ring functional groups contained in sodium humate and the modified graphene are used to improve the dispersion effect of the modified graphene in the matrix through π-π interaction.
[0021] 3. In the technical solution of the present invention, the nano-shielding material is modified using a silane coupling agent to prepare a modified nano-shielding material. The molecular structure of the silane coupling agent contains organic groups and silane groups, which can form chemical bonds with the nano-shielding material and the thermoplastic polymer matrix, thereby enhancing the interaction between them. The modified nano-shielding material and modified graphene can form a shielding layer in the composite material, and jointly improve the X-ray absorption capacity of the material. In addition, the modified nano-shielding material and modified graphene can improve the mechanical properties of the composite material as a reinforcing phase. The functional groups of sodium humate can interact with the thermoplastic polymer matrix to enhance the interfacial bonding force, thereby improving the overall mechanical properties of the composite material. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The specific implementation methods of this application involve: Silane coupling agent: KH570.
[0024] High-density polyethylene: molecular weight 40,000-300,000, provided by Shenzhen Huachuang Plastic Raw Materials Co., Ltd.
[0025] Example 1 A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Take a graphene oxide raw material, use a reducing agent to reduce it, and prepare modified graphene. The specific operation is: Graphene oxide was placed in deionized water at a mass volume ratio of 1 g:100 mL, and centrifuged at 6000 rpm for 3 minutes. Subsequently, a reducing agent was added to the system and treated at 70°C for 8 hours to obtain modified graphene; wherein the reducing agent was 80wt% hydrazine hydrate solution, and the amounts of graphene oxide and reducing agent used were 1g:0.8g.
[0026] S2. Performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material, the specific operation is as follows: The nano-shielding material is placed in an 80wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated for 10 minutes at room temperature, the ultrasonic frequency is set to 20KHz, and then an acetic acid solution is added to adjust the pH value of the system to 3, a silane coupling agent is added, and the system temperature is increased to 70°C. After treatment for 8 hours, the solution is centrifuged at 3000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material; wherein the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 at a mass ratio of 1:3:1, and the particle size is 30nm; the mass ratio of the nano-shielding material, the acetic acid solution, and the silane coupling agent is 1:5:0.05.
[0027] S3, adding the modified graphene and modified nano-shielding material obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of 0.1 g:0.1 g:5 mL, mixing at room temperature, then inputting into a blast drying oven and drying at 50° C. for 2 hours, mixing the dried product with a thermoplastic polymer matrix in a mass ratio of 10:70 and at a rate of 30 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing, thereby obtaining a thermoplastic composite material capable of absorbing X-rays; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0028] Example 2 A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Take a graphene oxide raw material, use a reducing agent to reduce it, and prepare modified graphene. The specific operation is: Graphene oxide was placed in deionized water at a mass volume ratio of 1 g:100 mL, and centrifuged at 7000 rpm for 5 minutes. Subsequently, a reducing agent was added to the system and treated at 80°C for 12 hours to obtain modified graphene; wherein the reducing agent was 80wt% hydrazine hydrate solution, and the amount of graphene oxide and the reducing agent used was 1g:1.0g.
[0029] S2. Performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material, the specific operation is as follows: The nano-shielding material is placed in an 85wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated for 20 minutes at room temperature, the ultrasonic frequency is set to 20KHz, and then an acetic acid solution is added to adjust the pH value of the system to 4, a silane coupling agent is added, and the system temperature is increased to 90°C. After treating for 8-10 hours, the solution is centrifuged at a rate of 3000-5000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material; wherein the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 at a mass ratio of 1:4:1.5, and the particle size is 40nm; the mass ratio of the nano-shielding material, the acetic acid solution, and the silane coupling agent is 1:5:0.07.
[0030] S3, adding the modified graphene and modified nano-shielding material obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of 0.5 g:0.5 g:7 mL, mixing at room temperature, then inputting into a forced air drying oven and drying at 70° C. for 2.5 hours, and then mixing the dried product with a thermoplastic polymer matrix in a mass ratio of 25:75 and at a speed of 60 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0031] Example 3 A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Take a graphene oxide raw material, use a reducing agent to reduce it, and prepare modified graphene. The specific operation is: Graphene oxide was placed in deionized water at a mass volume ratio of 1 g:100 mL, and centrifuged at 9000 rpm for 5 minutes. Subsequently, a reducing agent was added to the system and treated at 90°C for 16 hours to obtain modified graphene; wherein the reducing agent was 80wt% hydrazine hydrate solution, and the amounts of graphene oxide and the reducing agent used were 1g:1.2g.
[0032] S2. Performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material, the specific operation is as follows: The nano-shielding material is placed in a 90wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated for 30 minutes at room temperature, the ultrasonic frequency is set to 22KHz, and then an acetic acid solution is added to adjust the pH value of the system to 4, a silane coupling agent is added, and the system temperature is increased to 90°C. After treating for 10 hours, the solution is centrifuged at a speed of 5000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material; wherein the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 at a mass ratio of 1:3:2, and the particle size is 30-60nm; the mass ratio of the nano-shielding material, the acetic acid solution, and the silane coupling agent is 1:5:0.1.
[0033] S3, adding the modified graphene and modified nano-shielding material obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of 1 g: 1 g: 10 mL, mixing at room temperature, and then inputting into a forced air drying oven to dry at 80° C. for 3 hours, and then mixing the dried product with a thermoplastic polymer matrix in a mass ratio of 40:80 and at a speed of 90 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the nano shielding material in this comparative example is obtained by mixing Gd2O3 and Bi2O3 in a mass ratio of 1:4.
[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that the nano-shielding material in this comparative example is Bi2O3.
[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that no modified graphene is added in this comparative example, specifically: A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material, the specific operation is as follows: The nano-shielding material is placed in an 80wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated for 10 minutes at room temperature, the ultrasonic frequency is set to 20KHz, and then an acetic acid solution is added to adjust the pH value of the system to 3, a silane coupling agent is added, and the system temperature is increased to 70°C. After treatment for 8 hours, the solution is centrifuged at 3000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material; wherein the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 at a mass ratio of 1:3:1, and the particle size is 30nm; the mass ratio of the nano-shielding material, the acetic acid solution, and the silane coupling agent is 1:5:0.05.
[0037] S3, adding the modified nano-shielding material obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL at a mass volume ratio of 0.2 g:5 mL, mixing at room temperature, then inputting into a forced air drying oven and drying at 50° C. for 2 hours, mixing the dried product with a thermoplastic polymer matrix at a mass ratio of 10:70 and a speed of 30 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0038] Comparative Example 4 The difference between this comparative example and Example 1 is that the graphene oxide is not modified in this comparative example, specifically: A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material, the specific operation is as follows: The nano-shielding material is placed in an 80wt% ethanol solution at a mass ratio of 1g:5g, and ultrasonically treated for 10 minutes at room temperature, the ultrasonic frequency is set to 20KHz, and then an acetic acid solution is added to adjust the pH value of the system to 3, a silane coupling agent is added, and the system temperature is increased to 70°C. After treatment for 8 hours, the solution is centrifuged at 3000rpm for 5 minutes, the precipitate is collected, washed with deionized water, and dried at 105°C with a blower to obtain a modified nano-shielding material; wherein the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 at a mass ratio of 1:3:1, and the particle size is 30nm; the mass ratio of the nano-shielding material, the acetic acid solution, and the silane coupling agent is 1:5:0.05.
[0039] S3, adding the modified nano-shielding material and graphene oxide obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of 0.1 g:0.1 g:5 mL, mixing at room temperature, then inputting into a forced air drying oven and drying at 50° C. for 2 hours, mixing the dried product with a thermoplastic polymer matrix in a mass ratio of 10:70 and at a rate of 30 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0040] Comparative Example 5 The difference between this comparative example and Example 1 is that the nano shielding material is not modified in this comparative example, specifically: A method for preparing a thermoplastic composite material capable of absorbing X-rays comprises the following preparation steps: S1. Take a graphene oxide raw material, use a reducing agent to reduce it, and prepare modified graphene. The specific operation is: Graphene oxide was placed in deionized water at a mass volume ratio of 1 g:100 mL, and centrifuged at 6000 rpm for 3 minutes. Subsequently, a reducing agent was added to the system and treated at 70°C for 8 hours to obtain modified graphene; wherein the reducing agent was 80wt% hydrazine hydrate solution, and the amounts of graphene oxide and reducing agent used were 1g:0.8g.
[0041] S3, adding the modified graphene and nano-shielding material obtained in step S1 to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of 0.1 g:0.1 g:5 mL, mixing at room temperature, then inputting into a forced air drying oven and drying at 50° C. for 2 hours, mixing the dried product with a thermoplastic polymer matrix in a mass ratio of 10:70 and at a rate of 30 rpm to obtain a mixture; inputting the mixture into a hot pressing mold for pressing, thereby obtaining a thermoplastic composite material capable of absorbing X-rays; Among them, the nano-shielding material is obtained by mixing Gd2O3, Bi2O3, and LaB6 in a mass ratio of 1:3:1, and the particle size is 30nm; Wherein, the thermoplastic polymer matrix is high-density polyethylene.
[0042] Performance Testing The thermoplastic composite materials prepared in Examples 1-3 and Comparative Examples 1-5 of the present application were made into samples with a specification of 8cm*2cm*0.1cm. The tensile strength, elastic modulus (Young's modulus) and elongation at break of the composite materials were tested using an electronic universal material mechanical properties testing machine. The tensile rate was set to 8mm / min. The LX-D-2 Shore hardness tester was used for testing, and 5 test points were selected for each sample, and the average value was taken as the final hardness value. The specific test results are shown in Table 1 below.
[0043] Table 1 Group Tensile strength (MPa) Elastic modulus (MPa) Elongation at break (%) Hardness (HA) Example 1 17.2 1006.3 8.0 73.5 Example 2 18.0 1198.3 8.2 75.3 Example 3 17.8 1182.0 8.2 75.0 Comparative Example 1 17.1 1002.9 7.8 73.5 Comparative Example 2 17.2 1005.4 7.9 73.4 Comparative Example 3 15.3 899.8 7.1 78.9 Comparative Example 4 20.3 1112.5 3.9 83.9 Comparative Example 5 16.2 978.8 7.5 73.5 It can be seen from the results in Table 1 that the thermoplastic composite material prepared in Example 2 has the best mechanical properties. It can be seen from the data in Comparative Examples 1 and 2 that the use of composite shielding materials can increase the types of chemical bonds in the system, improve the uniformity between the components in the matrix, and make the product exhibit better mechanical properties. It can be seen from the results in Comparative Example 3 that without adding modified graphene to the system, the proportion of shielding materials increases, the hardness of the material increases, but the toughness of the product decreases, which limits its processing and application. It can be seen from the results in Comparative Example 4 that graphene oxide forms more cross-linking points in the thermoplastic matrix, the tensile strength is improved, and the elongation at break is reduced; the modified graphene and the modified nano-shielding material have a better fusion effect in the matrix, and the mechanical properties are improved. It can be seen from the results in Comparative Example 5 that the use of a silane coupling agent to modify the nano-shielding material can improve the overall mechanical properties of the material.
[0044] The X-ray shielding effect of the thermoplastic composites prepared in Examples 1-3 and Comparative Examples 1-5 is now tested. A PXS5-822 micro-focused 80 kV X-ray source, a lead chamber and a multifunctional radiation measuring instrument are used to form a test device. The circular sample is tested, the cross-sectional radius of the lead chamber is 15 cm, the diameter of the exit hole is 1 cm, and the source is 30 cm away from the exit hole. The shielding effect (S 70% , the thickness of the material required when the X-ray shielding rate is 70%) and the linear attenuation coefficient. Each sample was measured 5 times and the average value was recorded. The test results are shown in Table 2 below.
[0045] Table 2 Group S70% (cm) Linear attenuation coefficient (cm-1) Example 1 15.8 0.071 Example 2 14.6 0.086 Example 3 15.2 0.079 Comparative Example 1 16.0 0.068 Comparative Example 2 16.2 0.067 Comparative Example 3 18.3 0.053 Comparative Example 4 17.9 0.058 Comparative Example 5 17.6 0.060 From the test results of X-ray shielding effect in Comparative Examples 1-3 in the above table, it can be seen that the compounding of Gd2O3, Bi2O3, LaB6 and modified graphene in the nano-shielding material can improve the shielding effect of the material against X-rays. Gd, Bi and La, as materials with high atomic numbers, absorb X-rays mainly through mechanisms such as photoelectric effect and Compton scattering. Graphene, through its high conductivity and unique electronic structure, converts the absorbed X-ray energy into other forms of energy, further enhancing the shielding effect. From the results in Comparative Examples 4-5, it can be seen that after the modification of graphene and nano-shielding materials, the shielding effect of the resulting product is improved.
[0046] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0047] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a thermoplastic composite material capable of absorbing X-rays, characterized in that: The method comprises the following preparation steps: S1, taking a graphene oxide raw material, reducing it with a reducing agent, and preparing modified graphene; S2, performing hydrophobic modification on the nano-shielding material to prepare a modified nano-shielding material; S3, mixing the modified graphene, modified nano-shielding material and sodium humate solution obtained in step S1, and then inputting them into a forced air drying oven to dry at 50-80°C for 2-3 hours, and then mixing them with a thermoplastic polymer matrix to obtain a mixture; inputting the mixture into a hot pressing mold for pressing to obtain a thermoplastic composite material capable of absorbing X-rays.
2. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 1, characterized in that: In step S1, the modified graphene is specifically prepared by the following steps: The graphene oxide is placed in deionized water and centrifuged for 3-5 minutes, and then a reducing agent is added to the system and treated at 70-90° C. for 8-16 hours to obtain modified graphene.
3. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 2, characterized in that: The usage amount of graphene oxide and reducing agent is 1g:(0.8-1.2)g.
4. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 1, characterized in that: In step S1, the reducing agent used is 80wt% hydrazine hydrate solution.
5. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 1, characterized in that: The modified nano shielding material is specifically prepared by the following steps: The nano-shielding material is placed in an ethanol solution and ultrasonically treated for 10-30 minutes at room temperature, then the pH value of the system is adjusted to 3-4, a silane coupling agent is added, and the system temperature is increased to 70-90°C. After treatment for 8-10 hours, the solution is centrifuged, the precipitate is collected, washed, and dried to obtain the modified nano-shielding material.
6. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 5, characterized in that: The nano shielding material is obtained by mixing Gd2O3, Bi2O3 and LaB6 in a mass ratio of 1:(3-5):(1-2), and the particle size is 30-60nm.
7. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 5, characterized in that: The mass ratio of the nano-shielding material, the acetic acid solution and the silane coupling agent is 1:5:(0.05-0.1).
8. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 1, characterized in that: In step S3, the mixed material is specifically prepared by the following steps: The modified graphene and modified nano-shielding material obtained in step S1 are added to a sodium humate solution with a concentration of 0.5 g / mL in a mass volume ratio of (0.1-1) g: (0.1-1) g: (5-10) mL, mixed at room temperature, and then input into a forced air drying oven and dried at 50-80° C. for 2-3 hours. The dried product is then mixed with a thermoplastic polymer matrix in a mass ratio of (10-40): (70-80) and a speed of 30-90 rpm to obtain a mixture.
9. The method for preparing a thermoplastic composite material capable of absorbing X-rays according to claim 1, characterized in that: In step S3, the thermoplastic polymer matrix is high-density polyethylene.
10. A thermoplastic composite material obtained by the method for preparing a thermoplastic composite material capable of absorbing X-rays as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of graphene / lead oxide composite modified waterborne polyurethane material
CN107641314A
Nuclear ray protection glove and preparation method thereof
CN115058070A
X-ray shielding coating, preparation method and medical material containing X-ray shielding coating
CN117071294A
Lead-free ionizing radiation protection composite material and preparation method thereof
CN118879035A
Rare earth modified leadless X-ray shielding plastic
CN1789319A
Cited By
Special cable for acid and alkali resistant kiln and preparation method thereof
CN120209473A